IN CAPSULE: SAWS AND SEX MORES AMONG THE IGBO OF NIGERIA - Ezzeh, Peter-Jazzy (Proverbium - Yearbook, 2013)
The study is a rare attempt to study proverbs and related forms as repositories of the traditional worldview of the Okposi, an Igbo of Nigeria’s glottocultural group, on sex and sex-related matters. This effort has both academic and practical relevance. This is an under-explored area which should add to how much paremiologists know at present in this interesting form in the human speech art. At a practical level, understanding autochthonous sexual ideology of a group has important implications for reproductive health and appreciation of human sexuality in general. Igbo language is spoken indigenously by up to 40 million people. The lexicons of its 300 odd dialects can differ markedly in many respects. In an unhurried participant observation for the purpose of this study spanning five years (2005 to 2010) I collected 53 naturally situated utterances; 39 refer to sex and 14 were used for comparative purposes. It seems advisable to focus on proverbs and allied forms in this essay because of the audience. I am a native speaker of the dialect and a career anthropologist. I transcribe each utterance as collected before giving its English equivalent.